Non-specific neural stimuli and metabolic rhythms in rats - Van Der Touw, J; Thrower, S J; Olley, J (Physiologia Bohemoslovaca, 1978)
Ten rats housed in individual metabolism cages in a room next to a teaching laboratory showed rhythmic fluctuations in urination and defaecation. Sectral analysis of the data indicates a weekly rhythm which is attributed to the lack of neural stimuli at the weekend. Regression analysis using a weekly cycle illustrates this effect.
Keywords: Environment; krysa rodu Rattus; Animals; periodicita; životní prostředí; močení; zvířata; Urination; Periodicity; defekace; Rats; Defecation